2008
DOI: 10.1177/003804070808100201
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement, Peer Social Capital, and School Dropout Among Mexican American and Non-Latino White Students

Abstract: Policy makers are especially concerned about persistently high dropout rates among U.S. Latinos, the largest minority population in the United States. This study used a national longitudinal database to show that the behavioral and social aspects of schooling are dynamically linked in the process of school completion and dropout among Mexican American and non-Latino white adolescents. In contrast to the tendency of academically disengaged students to develop street-oriented friendships, students who are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
194
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(218 citation statements)
references
References 109 publications
9
194
1
7
Order By: Relevance
“…High dropout students showed that their exchanges with their peers were mainly focused on receiving and offering emotional support, while high success students exchanged also a great amount of information and academic support. These results are consistent with those found by Ream and Rumberger (2008) and Swenson, Nordstrom, and Hiester (2008), who claimed that "peer social capital" is a protective factor against dropout and fosters academic engagement. As for the size of the networks, it has also been seen a relationship between small and dispersed networks and school abandonment, so that actions such as mentoring programs (MBF, 2010;Rhodes & Lowe, 2008) or service-learning (Luna, 2012) may contribute to broaden their networks and contexts of relationship.…”
Section: Transition Risksupporting
confidence: 92%
See 1 more Smart Citation
“…High dropout students showed that their exchanges with their peers were mainly focused on receiving and offering emotional support, while high success students exchanged also a great amount of information and academic support. These results are consistent with those found by Ream and Rumberger (2008) and Swenson, Nordstrom, and Hiester (2008), who claimed that "peer social capital" is a protective factor against dropout and fosters academic engagement. As for the size of the networks, it has also been seen a relationship between small and dispersed networks and school abandonment, so that actions such as mentoring programs (MBF, 2010;Rhodes & Lowe, 2008) or service-learning (Luna, 2012) may contribute to broaden their networks and contexts of relationship.…”
Section: Transition Risksupporting
confidence: 92%
“…Selecting the main contributions from some of the papers reviewed (Gracia, Herrero, & Musitu, 2002;Lopez et al, 2007), this instrument analyses different aspects that encompass social support: a) contexts (community involvement, social networks and intimate relationships); b) type of support (informational, tangible and emotional); and c) the perceived reciprocity for each of these types of support. Another item was also included, which is of paramount interest to our study and in line with new research, the importance of social peer capital (Ream & Rumberger, 2008;Swenson, Nordstrom, & Hiester, 2008) in student engagement (item 25).…”
Section: Dimensions and Indicators Of Analysismentioning
confidence: 99%
“…An environment with positive peer and adult influences strengthens the adolescents' commitment to school and decreases their probability of drug use. Ream and Rumberger (2008) also studied the effects of participation in extracurricular activities on Mexican American students and documented that the students who participated in such activities were more likely to stay in school and be academically successful than were students who had not participated in extracurricular activities. Adolescents' sense of connectedness to their school has been attributed by several researchers as an important predictor of school success (Brown & Evans, 2002;Caskey, 2006).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In addition, more than two-thirds (69%) of Hispanic students attending public schools are of Mexican origin (Fry & Gonzales, 2008). Hispanics, as a group, tend to have the lowest levels of educational attainment and the highest dropout rate in the nation (Ream & Rumberger, 2008; U.S. Department of Education, National Center for Education Statistics, 2005). Furthermore, Hispanic students' academic struggles have resulted in an achievement gap with White and Asian American students that persists year after year (Austin, Hanson, Bono, & Cheng, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…School engagement was included in many dropout theories, but not often considered in empirical research (see e.g. Ream and Rumberger 2008). However, Finn's (1989) identification-participation model stated that active participation in school and a feeling of identification with school, strongly mediates school outcomes.…”
Section: Introductionmentioning
confidence: 99%